Honorary authorship in health sciences: a protocol for a systematic review of survey research - Reint Meursinge Reynders; Gerben ter Riet; Nicola Di Girolamo; Mario Malički (Systematic Reviews, 2022)
Abstract Background Honorary authorship refers to the practice of naming an individual who has made little or no contribution to a publication as an author. Honorary authorship inflates the output estimates of honorary authors and deflates the value of the work by authors who truly merit authorship. This manuscript presents the protocol for a systematic review that will assess the prevalence of five honorary authorship issues in health sciences. Methods Surveys of authors of scientific publications in health sciences that assess prevalence estimates will be eligible. No selection criteria will be set for the time point for measuring outcomes, the setting, the language of the publication, and the publication status. Eligible manuscripts are searched from inception onwards in PubMed, Lens.org , and Dimensions.ai. Two calibrated authors will independently search, determine eligibility of manuscripts, and conduct data extraction. The quality of each review outcome for each eligible manuscript will be assessed with a 14-item checklist developed and piloted for this review. Data will be qualitatively synthesized and quantitative syntheses will be performed where feasible. Criteria for precluding quantitative syntheses were defined a priori. The pooled random effects double arcsine transformed summary event rates of five outcomes on honorary authorship issues with the pertinent 95% confidence intervals will be calculated if these criteria are met. Summary estimates will be displayed after back-transformation. Stata software (Stata Corporation, College Station, TX, USA) version 16 will be used for all statistical analyses. Statistical heterogeneity will be assessed using Tau2 and Chi2 tests and I 2 to quantify inconsistency. Discussion The outcomes of the planned systematic review will give insights in the magnitude of honorary authorship in health sciences and could direct new research studies to develop and implement strategies to address this problem. However, the validity of the outcomes could be influenced by low response rates, inadequate research design, weighting issues, and recall bias in the eligible surveys. Systematic review registration This protocol was registered a priori in the Open Science Framework (OSF) link: https://osf.io/5nvar/ .